FT-IR Spectroscopic Investigation of Hofmann Td-Type Complexes of 2-, and 3-Chloropyridine - Bakiler, Meriç; Andreeva, Liljana; Minceva Sukarova, Biljana; AKYÜZ, SEVİM (Kluwer Academic Publisher, 2004)
Hofmann-type modified clathrate hosts containing 2- or 3-chloropyridine molecules attached to metal (II) tetracyanocadmate frame, with a given formula: M(Clpy)2Cd(CN)4 where M = Mn, Ni or Cd; Clpy = 2- or 3-chloropyridine, have been synthesised for the first time. Their FT-IR spectra are reported in the 400–4000 cm-1 region. All the vibrational modes of coordinated Clpy are characterised. The spectral features of the compounds studied are found to be similar to each other indicating that they have analogous structures. The coordination effect on the Clpy modes is analyzed.
Keywords: chloropyridine; Hofmann-type complexes; IR spectra; tetracyanometallate